Effect of substrate on the atomic structure and physical properties of thermoelectric Ca3Co4O9 thin films - BOYRAZ, CİHAT (IOP PUBLISHING LTD, 2011)
The incommensurately layered cobalt oxide Ca3Co4O9 exhibits an unusually high Seebeck coefficient as a polycrystalline bulk material, making it ideally suited for many high temperature thermoelectric applications. In this paper, we investigate properties of Ca3Co4O9 thin films grown on cubic perovskite SrTiO3, LaAlO3, and (La0.3Sr0.7)(Al0.65Ta0.35)O-3 substrates and on hexagonal Al2O3 (sapphire) substrates using the pulsed laser deposition technique. X-ray diffraction and transmission electron microscopy analysis indicate strain-free growth of films, irrespective of the substrate. However, depending on the lattice and symmetry mismatch, defect-free growth of the hexagonal CoO2 layer is stabilized only after a critical thickness and, in general, we observe the formation of a stable Ca2CoO3 buffer layer near the substrate-film interface. Beyond this critical thickness, a large concentration of CoO2 stacking faults is observed, possibly due to weak interlayer interaction in this layered material. We propose that these stacking faults have a significant impact on the Seebeck coefficient and we report higher values in thinner Ca3Co4O9 films due to additional phonon scattering sites, necessary for improved thermoelectric properties.
Keywords: THERMOPOWER; DEVICES